Obsahová analýza / formální obsahová analýza / kvantitativní obsahová analýza - Ilona Dvořáková (AntropoWebzin, 2010)
Content analysis is one of the basic tools used for quantitative treatment of data. Its theoretical framework was developed mainly in connection with American sociology of communication during the second half of 20th century. The aspiration to objectivity and systematic quantitative grasp of text and visual contents as well as emphasis on semantic and contextual evaluation is responsible for heterogeneous and arguable definitions of the field. Concrete applications of content analysis are therefore shaped by the nature of analysed data and researcher's individual goals even though basic methodological ground is maintained (i. e. selecting the data set, defining units of analysis and coding, operationalization of coding etc.). This broad concept of content analysis reflects its development in terms of sociology of communication and its different paradigms. Discussion and most frequent criticism of content analysis comprises different views of suitability of the selected data set, objectivity and validity, reliability, connection to quantitative methods, ability to make use of software etc. Despite the quantitative nature of content analysis there are still some qualitative aspects. One of possible and recently increasingly acknowledged concepts sees content analysis as specific approach to data which aims to quantification of data with taking some simple qualitative techniques into account.